Retirement financial wellness index: Conceptual framework and research agenda - Basar, Mohd Nur Fadzly; Noraina Mazuin, Sapuan (2022)
With a rapidly ageing society, Malaysia need to design new comprehensive policies that will ensure its people to have adequate financial protection in golden age RFW Index aims at providing guidance for the government, employers and future retirees in measuring employees’ preparedness for their retirement. This index will produce inputs for the government to develop the policies that will allow Malaysian to work longer with less physical demanding occupations and more digitally enabled working environment.